Comparative transcriptome analysis reveals a fetal origin for mesenchymal stem cells and novel fetal surface antigens for noninvasive prenatal diagnosis - Shun-Long Weng; Shing-Jyh Chang; Yi-Chieh Cheng; Hua-Yong Wang; Tao-Yeuan Wang; Margaret Dah-Tsyr Chang; Hsei-Wei Wang (Elsevier, 2011)
Objective: Mesenchymal stem cells (MSCs) are an attractive source for providing the cells necessary for regenerating damaged tissues. Fetal MSCs (fMSCs) are known to proliferate fast and have an excellent osteogenic capacity, yet the underlying mechanisms need to be explored. A better understanding of MSCs from different anatomic origins and ages will eventually benefit cell-based therapies, as well as subsequent mechanistic studies in the field of stem cell biology. Materials and Methods: We identified the molecular signatures of fetal and adult MSCs via a meta-analytic strategy and compared the enriched canonical pathways and genetic networks within each signature. Results: Fetal MSCs were found to express more cell cycle genes, which is consistent with the results of wetlab functional assays. In addition, the genes involved in vasculogenesis, neurogenesis, Wnt, MAPKKK pathways, and RNA splicing were found to be enriched in fMSCs. Correlating with the overexpression of multilineage differentiation genes, fMSCs share more genes with embryonic stem cells (ESCs) and are, therefore, more primitive. Further exploration into the transcriptome similarities revealed that MSCs from umbilical cord blood (UCB) express dominant fMSC genes, but not adult genes, suggesting a fetal origin for UCB MSCs. Novel surface proteins that were dominantly expressed in fetal and UCB MSCs, but not in adult MSCs or maternal PBMCs, were also identified. Conclusion: Our results systematically revealed the underlying genes and regulatory networks of two MSCs from unique origins, the resulting phenotypes, as well as the origin of UCB MSCs. The novel membrane proteins on the fetal MSC surface are promising candidate biomarkers for positively isolating fetal MSCs from maternal blood for noninvasive prenatal diagnosis.